The Role of Bile Acid in Improving Glucose Tolerance of Non-Obese Diabetic Rats After Proximal Small Bowel Bypass - Zheng, Zhihua; Pang, Qiang; Luo, Xin; Tao, Fang; Duan, Jinyuan; Cao, Jiaqing (Frontiers in Physiology, 2022)
An increase in bile acid (BA) levels after metabolic surgery is an important mechanism for improving glucose metabolism. However, the mechanisms underlying elevated BA levels and the regulatory mechanism of glucose metabolism remain unclear. In this study, we used the Goto-Kakizaki rat model to investigate the mechanism of BA elevation by comparing side-to-side jejunoileal bypass plus proximal loop ligation (SSJIBL) and bile ileum diversion (BID) as well as to explore the mechanism of BA metabolism in regulating blood glucose. The results showed that the fed blood glucose of rats in both the SSJIBL and BID groups was significantly lower than that of the SHAM group on days 2 and 14 after the operation. The oral glucose tolerance test (OGTT) improved in the SSJIBL and BID groups at day 14 postoperatively. The expression of CYP27A1 in the livers of the SSJIBL and BID groups was significantly increased. In addition, total serum BA levels in the SSJIBL and BID groups were significantly increased. Moreover, serum levels of lithocholic acid (LCA) and deoxycholic acid (DCA) were significantly higher in the SSJIBL group than in the SHAM group and negatively correlated with the area under the glucose tolerance curve (AUC-OGTT). In conclusion, increased BA synthesis may be an important cause of elevated total serum BA levels, and LCA and DCA are closely associated with improved glucose metabolism.